2017
DOI: 10.18632/oncotarget.16084
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor cells promote the metastatic colonization of disseminated carcinoma cells by inducing systemic inflammation

Abstract: Circulating tumor cells (CTCs) have been studied well in the prognosis for malignant diseases as liquid biopsy, but their contribution to tumor metastasis is not clearly defined. Here we report that CTCs could promote the metastatic colonization of disseminated carcinoma cells by inducing systemic inflammation and neutrophil recruitment to pre-metastatic organs. Depletion of neutrophils in vivo could effectively abrogate the promoting effect of CTCs on tumor cell metastasis. In the presence of CTCs, the pro-tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…It was documented recently (20) that even a minimal number of circulating tumour cells elicit a systemic inflammatory status contributing to the promotion of tumour metastasis. These circulating tumour cells represent a clinically undetectable disease burden.…”
Section: Introductionmentioning
confidence: 99%
“…It was documented recently (20) that even a minimal number of circulating tumour cells elicit a systemic inflammatory status contributing to the promotion of tumour metastasis. These circulating tumour cells represent a clinically undetectable disease burden.…”
Section: Introductionmentioning
confidence: 99%
“…IL-37 was able to suppress CTC-induced conversion of neutrophil function to pro-tumor phenotype. These findings suggest anti-inflammatory therapy could be used when higher CTC count is detected 66…”
Section: Extravasation and Colonization Of Distant Tissuesmentioning
confidence: 85%
“…Another factor might be the induction of inflammation, as described by the De Cock et al 65. In 2017, a Chinese study similarly reported that CTC-mediated systemic inflammation and neutrophil recruitment to pre-metastatic tissues is the mechanism of metastatic colonization by the CTCs 66. This was demonstrated in vitro using an anti-inflammatory cytokine interleukin 37 (IL-37) to deplete neutrophils, suppress inflammatory response and thus the promoting effect of CTCs on tumor metastasis 66.…”
Section: Extravasation and Colonization Of Distant Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is still largely unknown and is a subject of debate for the mechanisms determining the metastatic cell fate. Drawing inspiration from literature that transplantation of metastatic tumor cells to mice can lead to enrichment and augment in metastasis 10 , 12 , 13 , we established a bone-metastatic triple-negative breast cancer cell subline by transplanting a widely-used cell line, MDA-MB-231, to the fad pat of female nude mice to grow tumors in vivo . The bone metastatic cell sublines exhibited higher rate of proliferation, migration, invasion and bone metastasis.…”
Section: Introductionmentioning
confidence: 99%